2011, No. 10, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Auditing theory and practice Lionius Gaižauskas, Understanding the total cost of ownership, 7 Dalia Daujotaitė, Performance audit model based on the evaluation of financial management processes, 15 Andrejus Lebedevas, Application of management assertion in audit of profit (loss) statement, 25 Jonas Mackevičius, Jokūbas Leipus, Significance of audit in banks of Islamic countries, 38 Accounting theory and practice Erika Ragauskienė, States’ assets: accounting and status analysis, 53 Agnė Marfinaitė, Kristina Rudžionienė, Measurement and disclosure of an enterprise’s intellectual capital, 66 Jonas Mackevičius, Romualdas Valkauskas, The role of Jonas Ilgūnas in the creation of accounting system in Lithuania, 74 Economical problems Martynas Vanagas, Asta Strolaitė, Accounting regulation of European Union structural funds projects‘ under the program for 2007 - 2013, 85 Vytautas Kindurys, Theoretical and methodological aspects of insurance customers‘ loyalty, 99 Reviews Jonas Mackevičius, Theoretical and practical aspects of investment management, 112